Jon Stratton, Jon Dale and Tony Mitchell, eds., An Anthology of Australian Albums: Critical Engagements. (31st December 2020) - Homan, Shane
Abstract : Jon Stratton, Jon Dale and Tony Mitchell, eds., An Anthology of Australian Albums: Critical Engagements. New York and London: Bloomsbury, 2020. 223 pp. ISBN 9781501339875 (hbk).